2011
DOI: 10.1111/j.1440-1819.2010.02166.x
|View full text |Cite
|
Sign up to set email alerts
|

Is a patient‐administered depression rating scale valid for detecting cognitive deficits in patients with major depressive disorder?

Abstract: Aims: Although cognitive deficits are a common and potentially debilitating feature of major depressive disorder (MDD), such subjective declines in cognitive function are seldom validated by objective methods as a clinical routine. The aim of this study was to validate the Taiwanese Depression Questionnaire (TDQ) for detecting cognitive deficits in a sample of drug-free patients with MDD. Methods:The subjects consisted of 40 wellcharacterized medication-free patients with MDD and 40 healthy controls. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…Our results are in line with studies that have revealed changes in attention, verbal fluency, memory and psychomotor speed (Bashir, Khade, Kosaraju, Kumar, & Rani, 2013;Hueng et al, 2011;Kertzman et al, 2010;Lampe, Sitskoorn, & Heeren, 2004;Moniz, De Jesus, Pacheco, Gonçalves, & Viseu, 2016;Roca et al, 2015;Rohling, Green, Allen, & Iverson, 2002), with the exception that in our study the differences in memory were not statistically significant. Therefore, our first hypothesis (i.e., that individuals with depression will perform more poorly than individuals without depression) was only partially confirmed.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with studies that have revealed changes in attention, verbal fluency, memory and psychomotor speed (Bashir, Khade, Kosaraju, Kumar, & Rani, 2013;Hueng et al, 2011;Kertzman et al, 2010;Lampe, Sitskoorn, & Heeren, 2004;Moniz, De Jesus, Pacheco, Gonçalves, & Viseu, 2016;Roca et al, 2015;Rohling, Green, Allen, & Iverson, 2002), with the exception that in our study the differences in memory were not statistically significant. Therefore, our first hypothesis (i.e., that individuals with depression will perform more poorly than individuals without depression) was only partially confirmed.…”
Section: Discussionsupporting
confidence: 93%
“…This may be explained by differential effects of fatigue (Peters, 1980). Also comma as expected (Bashir et al, 2013;Hill et al, 2004;Hueng et al, 2011;Kertzman et al, 2010;Lampe et al, 2004;Rohling et al, 2002;Swann et al, 1999), we found significant impairment in psychomotor speed between unipolar depressed subjects and controls. Psychomotor performance in depressed subjects may be further influenced by other factors, such as hospitalization status/duration, severity, subtype and duration of depression, and medication (Bashir et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Bashir and colleagues (2013) verified a significant speed impairment regarding patients on antidepressants. Therefore, there are researchers (e.g., Hueng et al, 2011;Meyer et al, 2006;Swann et al, 1999) who chose to study only drug-free depressive subjects to access more precisely the actual impact of the illness itself on psychomotor function. This may represent a limitation to our study, but, for ethical reasons, we could not assess the clinical sample of medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the TDQ had good validity in its cognitive/affective component. A case–control study detected cognitive deficits in drug-free patients with major depressive disorder 36 using the TDQ and found that the cognitive subdomain of the TDQ was correlated with cognitive function. The aforementioned study supports the satisfactory validity of the cognitive aspect of the TDQ, suggesting that it may accurately assess depression in cancer patients.…”
Section: Discussionmentioning
confidence: 99%